ANALISIS PERKEMBANGAN KEMAMPUAN KEUANGAN DAERAH KABUPATEN KAYONG UTARA PERIODE TAHUN 2008 2012 - B61110046, ABU BAKAR (Jurnal Ekonomi Daerah (JEDA), 2014)
ABSTRACT This research Analisis is Regency Region acceptance Jiabiiitv developing Kayong Is Period North Year 2008 2012 it aims to know and analyzed of condition and composition, financial growth, and degree Regency region acceptance liability Kayong Utara in period 2008 2012. Know and analyzed of self original revenue (PAD)'S North Kayong Regency to PDRB and resident (people). Variable that was analyzed is all original accepting component region (PAD), namely region taxes, region retribution, etc. propertied region which validates, Population, and PDRB/GRDP (Gross Regional Domestic Product) by use of data skunder that acquired of on duty Regency Region Revenue of North Kayong and BPS (North Kayong's regency In Number/Fegure). Result observationaling to point out that 1) Regions propertied composition Regency Kayong North dominated by transfer fund of center until up to average 89,19%, PAD 4,63% etc. propertied one validate 6,18%, but such PAD'S contribution tends to increase each year. Increasing it foots up PAD's North Kayong Regency kicked in by region taxes acceptance that tali, can be said that taxes payee quality just fine at North Kayong Regency. Degrees arithmetic result Decentralize North Kayong Regency Fiscal bottommost, averagely as big as 3,70 %. Usufructs PAD'S elasticity count to PDRB average as big as 0,291, and elasticity to resident average as big as 34,29. Its mean is changed or added islandic as big as 1 % make changing or added PAD as big as 34,29%. Key word: Financially Region, PAD, Composition, Elasticity.